Neuropsychiatric sequelae one year after a minor head injury - Deb, S. (BMJ Group, 1998)
OBJECTIVE—To assess neuropsychiatric sequelae 1 year after minor head injury in a cross sectional study using home interviews with patients and their relatives at 1 year after head injury. METHODS—The study cohort included 148 adults who were admitted to hospital after a minor head injury between 1 July 1994 and 30 June 1995 and showed clinical or radiological evidence of brain injury. Main outcome measures used in the study were the Glasgow outcome scale, Edinburgh rehabilitation status scale, Barthel index, clinical interview schedule-revised, mini mental state examination, and assessment of symptoms of postconcussional syndrome. RESULTS—At one year follow up, four (2.9%) patients had a severe disability, 35 (25.5%) had a moderate disability, and 95 (69.3%) had no disability according to the Glasgow outcome scale. A slightly higher proportion (33.3%, n=45) showed disability according to the Edinburgh rehabilitation status scale. Thirty one patients (23.1%) scored < 24 in the mini mental state examination. These were mostly patients over the age of 65. Twenty three patients (17.2%) were diagnosed as psychiatric cases according to the clinical interview schedule-revised scale. Seventy four (55.2%) patients showed one of the symptoms of postconcussional syndrome. The most commonly shown neurobehavioural problems were irritability (30%), sleep disturbance (29%), and impatience (27%). CONCLUSION—One year after a minor head injury, a substantial proportion of patients showed neuropsychiatric sequelae.